Kepastian Hukum Pengenaan BPHTB kepada Pemilik Tanah dan / atau Bangunan yang Belum Bersetifikat dalam Rangka Pendaftaran Tanah Sistematis Lengkap - Darmaini, Yohanna; Azminazilah, Azminazilah; Amiludin, Amiludin; Ahmad, Dwi Nurfauziah; Razif, Imran Bukhari (Faculty of Law Universitas Islam Indonesia, 2023)
Land is the most important agrarian aspect of a country which has cultural, political, social, and economic value. The need for registration by the land owner, where this registration is carried out at the land office can guarantee land control by a party by obtaining a land certificate. The certificate exists as proof that the party occupies and controls and has rights to the land. Disputes often lead to chaos or disparities due to commotion between communities fighting over land rights. Land Registration According to Article 1 Paragraph 1 of Government Regulation Number 24 of 1997 is the continuation of activities carried out by public bodies in a place that are continuous and regular, including sorting, handling, bookkeeping, as well as presenting and maintaining actual and juridical information. information, as a guide and note, regarding a collection of information. The Land Rights Registrar can revoke tax levies if there is valid evidence through an authentic deed of land maintenance and registration. This tax collection will later be deposited by the Land Rights Registrar to the regional revenue office usually abbreviated to the Regional Revenue Office to provide legal certainty and protection for interested parties. Land registration activities are a form of government concern and fees for registering land and building rights are a form of tax on land registration. This tax is to ensure the continuity of land rights owned by individuals or entities over that land.Key Word: Registration, Tax, Conflict, Dispute, Legal Certainty AbstrakTanah sebagai aspek agraria terpenting dalam negara yang mempunyai nilai budaya, politik, sosial dan ekonomi. Perlunya pendaftaran oleh pemilik tanah, dimana pendaftaran ini dilakukan pada kantor pertanahan dapat menjamin penguasaan tanah oleh suatu pihak dengan diperolehnya sertifikat tanah. Sertifikat tersebut ada sebagai bukti bahwa pihak tersebut menempati dan menguasai serta memiliki hak atas tanah. Sengketa seringkali menimbulkan kekacauan atau kesenjangan karena adanya keributan antar sesama masyarakat dalam memperebutkan hak atas tanah. Pendaftaran Tanah Menurut Pasal 1 Ayat 1 Peraturan Pemerintah Nomor 24 Tahun 1997 adalah kelanjutan kegiatan yang dilakukan oleh badan publik di suatu tempat yang bersifat terus menerus dan biasa, meliputi penyortiran, penanganan, pembukuan, serta penyajian dan pemeliharaan informasi yang aktual dan yuridis. Informasi, sebagai pedoman dan catatan, mengenai kumpulan informasi. Pencatat Hak Atas Tanah dapat mencabut pungutan pajak apabila terdapat bukti yang sah melalui akta otentik pemeliharaan dan pendaftaran tanah. Pemungutan pajak inilah yang nantinya disetorkan oleh Pencatat Hak Atas Tanah kepada kantor pendapatan daerah atau biasa disingkat Kantor Pendapatan Daerah untuk memberikan kepastian hukum dan perlindungan bagi pihak-pihak yang berkepentingan. Kegiatan pendaftaran tanah sebagai wujud kepedulian pemerintah dan biaya pendaftaran hak atas tanah dan bangunan sebagai bentuk pajak atas pendaftaran tanah tersebut. Pajak tersebut untuk menjamin keberlangsungan hak atas tanah yang dimiliki oleh orang pribadi atau badan atas tanah tersebut.Kata-kata Kunci: Pendaftaran, Pajak, Konflik, Sengketa, Kepastian Hukum